Titania-Y-TZP biocomposites and their in vitro studies - Hoo, Pui Woon. (2008)
Bioactive ceramics have the ability to form chemical bonding with bone, resulting in good interfacial attachment between an implant and its surrounding bone. Sol-gel derived titania is known to be bioactive. The limitation of the current bioactive ceramics, including titania, is the lack of high mechanical properties. Yttria stabilised tetragonal zirconia polycrystals (Y-TZP), on the other hand, is well known for its good biocompatibility and high fracture toughness. Therefore, there is an interest to produce titania-Y-TZP composites, with the aim of achieving both desirable bioactivity and mechanical properties.